POTENTIAL ANALYSIS OF INDUSTRIAL WASTE USING SEVEN BASIC QUALITY TOOL PARETO DIAGRAM - Wiranto, Agus (Yayasan Education and Social Center, 2023)
The rapid development of the industrial sector in Indonesia today has an impact on other environments, both positive and negative impacts. The positive effects of industrial expansion are seen in sectors of the economy, many new jobs are created and many new applications for new technologies are used. The negative impact that cannot be avoided is caused by industrial waste, sometimes also caused by liquid waste containing substances that are harmful to the surrounding population. Every company must carry out industrial waste treatment from the negative impacts caused. PT TGLC, a company engaged in the manufacture of liquid sugar (glucose). In the process of producing liquid sugar (glucose) there is a regeneration process, namely the process of recovering the resin used in the ion exchanger column, which produces liquid waste in the process. Methods for dealing with the problem of industrial waste products, by identifying the contribution made by each system to the industrial data for all systems. The